The Influence of Brand Experience, Perceived Value, and Brand Trust on Brand Loyalty of Glad2Glow Products among Gen Z in Surabaya - Hany Susanti; Rizky Dermawan (Universitas KH. Abdul Chalim Mojokerto, 2026)
The skincare industry in Indonesia has experienced rapid growth, making skincare a routine necessity for modern society. Amidst increasing competition and reputational risks, companies must understand the factors influencing brand loyalty, particularly among the Gen Z segment, known for being critical and selective. This study aims to examine the influence of brand experience, perceived value, and brand trust on brand loyalty toward Glad2Glow products among Gen Z consumers in Surabaya. This study employs a quantitative research approach. This study utilized a sample of 112 respondents selected using non-probability method and purposive sampling technique, with criteria including respondents aged 17–27 years, residing in Surabaya, and and have purchased and used Glad2Glow skincare products at least twice. The data were then analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) with SmartPLS software, including validity, reliability, and hypothesis testing. The results indicate that Brand Experience, Perceived Value, and Brand Trust have a positive and significant influence on Brand Loyalty Glad2Glow product among Generation Z in Surabaya.